Removal of Alizarin Red Dye from Aqueous Solution with Bio Sorption Technique Using Snail Shell as Low Cost Adsorbent - Muneer A Al-Da'amy (Journal of Global Pharma Technology, 2018)
Study evaluated the feasibility of removing Alizarin Red dye from aqueous solutions, using snail shell. The effect of contact time, adsorbent does, pH, ionic strengthinitial dye concentration and temperature on adsorption was studied. The pH 2.0 was observed to show optimum removal for Alizarin Red. The equilibrium time was fixed at10min. Maximum adsorption of Alizarin Red was a achieved at the suggested optimum conditions initial dye concentration 30mg.l-1 weight of adsorbent 0.01g .The adsorption isotherms could be well-defined with the Temkin isotherm model instead of the Freundlich isotherm model. Change in entropy (ΔS°), Gibb’s free energy change (ΔG°), and enthalpy (ΔH°) were calculated for the adsorption of Alizarin Red dye.Keywords:  Adsorption, Alizarin Red, Snail shell, Langmuir, Freundlich, Temkin.